COVID-19 Case Investigation and Contact Tracing: Early Lessons Learned and Future Opportunities. (January 2021) - Ruebush, Elizabeth; Fraser, Michael R.; Poulin, Amelia; Allen, Meredith; Lane, J. T.; Blumenstock, James S.
Abstract : Context: Case investigation and contact tracing are fundamental public health strategies for controlling and preventing the spread of infectious diseases. Although the principles behind these strategies are not new, the capacity and operational requirements needed to support disease investigation during the SARS-CoV-2 (COVID-19) pandemic are unprecedented. This article analyzes the implementation of case investigation and contact tracing in controlling COVID-19 transmission during the early stages of the US pandemic response (January 20 through August 31, 2020). Program Implementation: Governmental public health agencies mobilized to expand case investigation and contact tracing programs in the early months of the pandemic. In doing so, they encountered a range of challenges that included rapidly scaling up the workforce; developing and subsequently revising guidance and protocols specific to COVID-19 as more was learned about the virus over time; defining job functions; encouraging public acceptance of and participation in case investigation and contact tracing; and assessing the utility of these activities during both the containment and mitigation phases of outbreak response. COVID-19 case investigation and contact tracing programs presented an array of opportunities for health departments to innovate, especially around technology to support public health efforts, as well as opportunities to address health equity and advance community resilience. Conclusion: Lessons learned from disease intervention specialists, guidance and resources from federal agencies and national partners, and peer-to-peer exchange of promising practices can support jurisdictions encountering early implementation challenges. Further research is needed to assess COVID-19 case investigation and contact tracing program models and innovations, as well as strategies for implementing these activities during containment and mitigation phases.